Peran dan Fungsi Humas dalam Publikasi pada Kantor Dinas Kelautan dan Perikanan Provinsi Sulawesi Selatan - Mahmud Mahmud; Fatmawati Fatmawati; Ismail Ismail (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The success of government publications to the public cannot be separated from the role of public relations (public relations). Public relations or better known as PR (Public Relations) has a very large role and is very much needed by leaders.